“Baneful Herbs.” Presented at It’s Only Natural, Artes & Craft, Hartford, MI, November 4, 2018 - Michael, Coby (New Age Movements, Occultism, and Spiritualism Research Library, 2018)
Slides from a presentation by Coby Michael on November 4, 2018 at the Artes & Craft, Hartford, Michigan. The workshop covered herbs found in traditional witchcraft with emphasis on their use for discovering the Poisoner’s Path and the dark aspects of the Divine. Each plant describes the astrological and planetary characteristics, their alchemical properties and how they relate to plant spirits.
Baneful Herbs
1 electronic record(s) bag with alternative formats and metadata. 2.26 MB. 2365985 bytes. 34 pages.
Keywords: Poisonous plants; Herbs; Poisonous plants--Mythology; Atropa (Plants); Solanum; Hyoscyamus niger; Cronos (Greek deity); Medicine, Magic, mystic, and spagiric